2016
DOI: 10.5535/arm.2016.40.6.1082
|View full text |Cite|
|
Sign up to set email alerts
|

Risk Factors for Delirium During Acute and Subacute Stages of Various Disorders in Patients Admitted to Rehabilitation Units

Abstract: ObjectiveTo assess the risk factors for delirium in patients admitted to a rehabilitation unit for acute or subacute neurological or musculoskeletal disorders.MethodsWe reviewed the medical records of 537 patients admitted to a rehabilitation unit and selected 398 patients in the acute or subacute stage of various neurological or musculoskeletal disorders. Among them, patients who had suffered from delirium were categorized into the delirium group (n=65), and the other patients were categorized into the non-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 37 publications
3
13
0
1
Order By: Relevance
“…However, fidelity audits confirmed that allied health service events increased by 27%‐36% on the experimental ward during the intervention. Another concern with ward changes in a setting with high rates of delirium is the disorientating effect that these changes can have on patients with a high risk of delirium . Clinical practice guidelines recommend against the practice of changing rooms and wards for patients with delirium .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, fidelity audits confirmed that allied health service events increased by 27%‐36% on the experimental ward during the intervention. Another concern with ward changes in a setting with high rates of delirium is the disorientating effect that these changes can have on patients with a high risk of delirium . Clinical practice guidelines recommend against the practice of changing rooms and wards for patients with delirium .…”
Section: Discussionmentioning
confidence: 99%
“…Another concern with ward changes in a setting with high rates of delirium 20 is the disorientating effect that these changes can have on patients with a high risk of delirium. 21 Clinical practice guidelines recommend against T A B L E 3 Discharge destination: number of participants (%) at each ward pre-and postintervention and odds ratio (95% CI) between wards the practice of changing rooms and wards for patients with delirium. 22 However, a sensitivity analysis excluding patients who changed wards during their GEM admission did not change our results.…”
Section: Discussionmentioning
confidence: 99%
“…In prior research, Jang reported that a decreased potassium concentration is independently associated with delirium in patients admitted to rehabilitation wards (OR = 0.144 [95% CI = 0.064-0.327], p < 0.001) [36]. In addition, disturbance of the balance of electrolytes such as sodium and potassium or glucose increases the risk of delirium after surgery [37,38].…”
Section: Postoperative Potassiummentioning
confidence: 98%
“…In a study, the mean age of patients with delirium (69.3±13.9 years) was signif icantly higher than in patients without delirium (63.5±16.5 years). In addition, there was no signif icant difference between the two groups in terms of gender (Jang ., 2016). Based on the results of the present study, although the incidence of delirium in patients aged over 65 years (50%) was higher than those aged under 65 years (38.15%), there was no signif icant relationship between…”
Section: Research Articlementioning
confidence: 99%